Zlepsuje záchyt onemocnĕní v asymptomatickém období prognózu pacientek s karcinomem endometria? - Kudela, M; Dzvincuk, P; Ondrová, D; Lubuský, M; Michnová, L (Ceska gynekologie, 2007)
OBJECTIVE: To analyse factors which led to the diagnosis of endometrial carcinoma in patients still in asymptomatic stage and to find out if such early diagnosis has an impact on further prognosis of this carcinoma. DESIGN: Retrospective study. SETTING: Department of Obstetrics and Gynecology, Medical Faculty of the Palacký University and University Hospital, Olomouc. METHODS: The analysis of reasons which made the patients with endometrial carcinoma to see a gynecologist and estimate the proportion of preventive measures in the diagnosis malignant diseases of uterine corpus. RESULTS: The study included 110 patients with diagnosis of endometrial carcinoma. The Common symptoms of endometrial carcinoma, e.g. most often irregular bleeding, brought 87 (79%) patients to gynecologists while in remaining 23 (21%) of patients the disease was found in asymptomatic stage at the preventive oncogynecologic examination or incidentally at the examination for other illnesses. Both groups differed in staging and grading. CONCLUSIONS: The asymptomatic patients where the disease was diagnosed incidentally or during preventive oncogynecologic examination had, in the beginning of treatment, markedly lower staging and more favorable grading than symptomatic patients, what generates preconditions for a better prognosis of these patients.
Keywords: Early Diagnosis; prognóza; Adult; Aged; dospělí; senioři; Endometrial Neoplasms; lidé; Carcinoma; ženské pohlaví; adenokarcinom; Humans; časná diagnóza; karcinom; Prognosis; Adenocarcinoma; Female; lidé středního věku; nádory endometria; Middle Aged